Vertical handoff reduction mechanism using IEEE 802.21 standard in mobile IPv6 (MIPv6) network - Masud, Mosharrof Hussain; Anwar, Farhat; Bari, S.M. Sadakatul; Mohamed, Omer Mahmoud (IRACST, 2012)
Low handoff latency and minimum packet loss are envisioned important factors for the next generation Mobile IPv6 (MIPv6) based heterogeneous networks. To meet these constraints IEEE 802.21-Media Independent Handover (MIH) was introduced to enhance the Quality of Service (QoS) of the networks. The MIH provides link layer information to the network layer to reduce handoff latency while the mobile node (MN) changes its active interface to another interface. In this paper an additional entity “Smooth Handoff Controller” (SHC) and an algorithm are proposed to select alternative interfaces in advance while MN is using an active interface. This mechanism helps the MN to configure additional interfaces that reduces handoff latency and packet loss. The simulation result shows better performance over the standard MIPv6. The proposed mechanism is simulated using OMNeT++. The simulation results show 70% reduction of handoff latency and 40% to 45% reduction of packet loss thus indicating a large improvement towards achieving better QoS.